Integrating the Prophet’s Parenting Model to Strengthen Student Character in the Digital Age: A Qualitative Study at SMPN 1 Payaraman - Suroso Suroso; Farida Husin; Wasitoh Meirani; Fifi Aura Amedita; Nabila Syahira; Hamdika Priyadi (Attractive : Innovative Education Journal, 2026)
Integrating the Prophet Muhammad’s parenting model into the modern education system is becoming increasingly urgent in the digital age, where students face moral fragmentation, excessive media exposure and a weakening of character development. This study explores how the Prophet Muhammad’s parenting model, derived from the Sunnah, can be integrated to strengthen pupils’ character at SMPN 1 Payaraman. The aim of this study is to analyse the form, process, and implications of integrating the Prophet’s parenting values within the context of a state lower secondary school. Using a single-case qualitative study design, data were collected through in-depth interviews with twelve participants (the headteacher, teachers, and students), non-participant observation over a three-month period, and document analysis comprising the school’s vision statement, lesson plans, and activity reports. Data were analysed using thematic analysis based on Braun and Clarke’s framework to identify patterns related to the implementation of the principles of the Prophet’s upbringing. The findings revealed three dominant character domains: (1) honesty (al-sidq) and trustworthiness (al-amanah), reflected in integrity-based programmes such as the honesty canteen and anti-cheating initiatives; (2) compassion (ar-rahmah) and respect (al-ihtiram), reflected in teacher-pupil interactions, peer mentoring, and restorative disciplinary approaches; and (3) the love of knowledge (thalab al-‘ilmi) and cleanliness, embedded in academic motivation and the school’s culture of cleanliness. Exemplary leadership (al-qudwah) demonstrated by the headteacher and teachers emerges as the primary mechanism for internalisation. This study concludes that integrating the Prophet Muhammad’s parenting model provides a contextual and effective framework for strengthening students’ character holistically in state schools amidst the challenges of the digital age